PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING PADA MATERI TRIGONOMETRI DI SMK SMTI NEGERI PONTIANAK - Simbolon, Perdi Dapot; Jamiah, Yulis; ahmad, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aims to know and describe the effectiveness of Contextual Teaching and Learning approach in the trigonometry topic at class XI of SMK SMTI Negeri Pontianak Mechanical Engineering Department. The aspects that want to be knowand describe are the implementation of the learning process, student’s learning activities, student’s respond and student’s outcomes. The research method is descriptive method. The research subject is students in class XI TP 2. Based on the data analysis from four aspects are: (1) the implementation of the learning process categorized very good with average score 3,73; (2) student’s learning activities categorized active (77,55%); (3) student’s respond categorized positive with 3 student (8%) give a very positive respond and 33 student (92%) give a positive respond; and (4) student’s outcome is not reached classical completness with only 75% of student can achieve the minimum completeness criteria. Because only three out of four aspects that achieved, the coclusion of this research is the implementation of Contextual Teaching and Learning approach less effective in the trigonometry topic at class XI TP 2 SMK SMTI Negeri Pontianak. Keywords: Contextual Teaching and Learning Approach, Trigonometry Subject, Effectiveness